Redesain Ruas Jalan Abdul Haris Nasution Sta 0+000 S/D Sta 2+500 Kec. Padangsidimpuan Tenggara Kota Padangsidimpuan - Ahmad Rafii; Tobi Vance Sunarto Siregar (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
The research on the Abdul Haris Nasution Road Redesign provides an in-depth insight into the required pavement thickness, which varies depending on the type of pavement applied. In this analysis, flexible pavement requires a more complex structure, consisting of a 15 cm thick surface layer, a 20 cm thick top foundation layer, and a 10 cm thick bottom foundation layer. The thickness is designed to effectively distribute the weight of the traffic load, thereby reducing the risk of damage to the road surface. For rigid pavement, the analysis shows that the required structure is simpler. Only a 20 cm thick concrete surface layer and a 10 cm thick lower foundation layer are required. This rigid pavement construction has advantages in terms of durability and the ability to withstand higher traffic loads, making it a more efficient option for the traffic conditions on Jalan Abdul Haris Nasution. Based on the results of the study, it is concluded that the most suitable construction type for Jalan Abdul Haris Nasution is rigid pavement. This assessment is based on the road classification, road function, and existing traffic conditions. Rigid pavement not only meets technical requirements, but provides economic and operational benefits in the long term. As such, this research provides an important reference in planning and developing more efficient and sustainable road infrastructure in the future.